2014
DOI: 10.1161/hypertensionaha.114.03614
|View full text |Cite
|
Sign up to set email alerts
|

Setting Thresholds to Varying Blood Pressure Monitoring Intervals Differentially Affects Risk Estimates Associated With White-Coat and Masked Hypertension in the Population

Abstract: Outcome-driven recommendations about time intervals during which ambulatory blood pressure should be measured to diagnose white-coat or masked hypertension are lacking. We cross-classified 8237 untreated participants (mean age, 50.7 years; 48.4% women) enrolled in 12 population studies, using ≥140/≥90, ≥130/≥80, ≥135/≥85, and ≥120/≥70 mm Hg as hypertension thresholds for conventional, 24-hour, daytime, and nighttime blood pressure. White-coat hypertension was hypertension on conventional measurement with ambul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
91
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 35 publications
(53 reference statements)
8
91
1
9
Order By: Relevance
“…Although any time interval suffices to diagnose masked hypertension, as proposed in current guidelines, full 24-hour recordings remain standard in clinical practice. 37 The higher 24-hour BP variability in subjects with whitecoat hypertension may help to explain the higher rates of cardiovascular risk that have been reported in previous studies of these patients. [33][34][35] BP variability depends on sympathetic vascular modulation and changes in arterial distensibility.…”
mentioning
confidence: 93%
“…Although any time interval suffices to diagnose masked hypertension, as proposed in current guidelines, full 24-hour recordings remain standard in clinical practice. 37 The higher 24-hour BP variability in subjects with whitecoat hypertension may help to explain the higher rates of cardiovascular risk that have been reported in previous studies of these patients. [33][34][35] BP variability depends on sympathetic vascular modulation and changes in arterial distensibility.…”
mentioning
confidence: 93%
“…Prior studies showed inconsistent results in cardiovascular outcomes between the patients with masked HTN and white-coat HTN. 16,32 We found significant increase in composite cardiovascular events and all-cause mortality Integrated Blood Pressure Control 2018:11 submit your manuscript | www.dovepress.com…”
mentioning
confidence: 74%
“…In 8,237 untreated persons, mean age 50.7 years, in 12 population studies, the prevalence of masked hypertension ranged from 9.7% to 19.6% (10). At followup, compared to normotensive persons, persons with masked hypertension had a 1.76 to 2.03 times increase in cardiovascular events (10).…”
mentioning
confidence: 99%
“…Masked hypertension was diagnosed by ambulatory blood pressure monitoring in 14% of persons and by home blood pressure monitoring by 11% of persons (6). It may be reasonable to screen for masked hypertension with ambulatory blood pressure monitoring or with home blood pressure monitoring if the office systolic blood pressure is 120 to 129 mmHg or if the office diastolic blood pressure is 75 to 79 mmHg (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%